A participação social na perspectiva dos(as) jovens protagonistas da ONG SOS adolescente - Reis, Denise Maria (2009)
This study has investigated, in the years 2007 to 2009, how eighteen young of social project Núcleo de Jovens Protagonistas of Non-Governmental Organization SOS adolescente from Campinas/SP city understand the social participation and the protagonists actions in the multiple spaces where they live, focusing on the educational processes that they experience, using a participatory methodology of qualitative research, through a critical-dialectical approach. The mode of educational action called Juvenile Protagonism, has emerged in a systematic way in the late 90's in the country, seeking to subvert the youth thematization as a social problem. Given the comments about the educational practice of that project and social studies that demonstrate a political action of youths supporting the consensus and more specific interventions, became important to investigate the problem from the perspective of young people named protagonist. The analysis was anchored in theoretical and methodological referencial which, far beyond criticism, qualifies knowledge and means of resistance of popular individuals or groups, researching and understanding the reality with them, taking the coexistence and dialogue as fundamental research procedures. Considering the dialectics of social reality, full of contradictions, as well as the institutional context in which they participate, the results presented by two thematic axles: to pass what you learn and make part and take part point to ambiguities or inconsistencies between words and actions of young, bypassing their ways of understanding the object of study. These modes are related to learning and teaching, with educational roles and commitments they assume to themselves and with other young ones who live in multiple spaces of social inclusion where the critical consciousness and transformative action are highly relevant because they establish as reasonable utopia the change of the world guided by values of solidarity and justice. Was still verified the occurrence of various educational processes with humanizing character that transcend the boundaries of the Juvenile Protagonism proposal, as well as a perspective of more egalitarian gender relations.